Vascular Endothelial Growth Factor (VEGF) Immunoreactivity Pattern in Different Cervical Cancer Types in a Tertiary Healthcare Facility in South Eastern Nigeria - Amalachukwu Okwukwe, Ike; Samuel Ifedioranma, Ogenyi; Elebua Okereke, Eric; Ramson Chinemerem, Achilefu; Christian Kelechi, Agwaraonye; Jonathan Uja, Madukwe; Ugochukwu Nyenke, Clement (Asian Pacific Journal of Cancer Biology, 2025)
Background: Cervical cancer remains a major public health issue in Nigeria. With advancements in treatment, there is a growing focus on targeted therapies. Vascular Endothelial Growth Factor (VEGF), a critical mediator of tumour angiogenesis, has emerged as a potential biomarker in cervical cancer for early detection and targeted therapies. Materials and Methods: This retrospective cross-sectional study was conducted in the Department of Histopathology, Nnamdi Azikiwe University Teaching Hospital, Nigeria. A total of 117 diagnosed cervical carcinoma cases were evaluated. VEGF expression was assessed through immunohistochemistry using a Bio-SB monoclonal antibody, with VEGF positivity indicated by brown membrane staining in tumour cells. VEGF expression was quantitatively measured by calculating the percentage of positively stained cells per high-power field, and results were categorized as positive or negative based on predetermined cut-off points. Patients’ clinicopathological data, including tumour type, grade, and cell differentiation, were also analyzed. Results: The mean ages of patients with adenocarcinoma, squamous cell carcinoma-in-situ, and invasive squamous cell carcinoma were 44.9, 54.3, and 55.9 years, respectively. VEGF positivity was observed in 65 (55.56%) of cases, with a statistically significant difference between positive and negative cases (P < 0.05). VEGF was expressed in 8 (53.33%) of adenocarcinoma cases, 17 (65.39%) of squamous cell carcinoma-in-situ cases, and 40 (52.63%) of invasive squamous cell carcinoma cases. The highest expression was observed in squamous cell carcinoma-in-situ, suggesting an early role in tumour angiogenesis. VEGF expression was more frequent in well- and moderately differentiated tumours compared to poorly differentiated ones. Among squamous cell carcinomas, VEGF positivity was higher in non-keratinizing tumours 36 (57.14%) than in keratinizing tumours 20 (51.28%). Conclusion: The study demonstrates that VEGF is significantly expressed in different histological subtypes of cervical cancer, particularly in early-stage tumours, highlighting its potential as a biomarker for early detection and targeted therapy. However, limitations include the retrospective nature of the study and potential variability in VEGF quantification. Future studies should focus on larger sample sizes and explore the role of VEGF in treatment outcomes to refine its utility as a therapeutic target.